2017
DOI: 10.1007/s10509-017-3205-x
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous accelerations in spacecraft flybys of the Earth

Abstract: The flyby anomaly is a persistent riddle in astrodynamics. Orbital analysis in several flybys of the Earth since the Galileo spacecraft flyby of the Earth in 1990 have shown that the asymptotic post-encounter velocity exhibits a difference with the initial velocity that cannot be attributed to conventional effects. To elucidate its origin, we have developed an orbital program for analyzing the trajectory of the spacecraft in the vicinity of the perigee, including both the Sun and the Moon's tidal perturbations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…In the context of this discussion we should also mention that similar anomalous accelerations are also found in several spacecraft flybys of the Earth [3]. In this case, they are only a 1.5 % of those found in the case of the Juno's flybys of Jupiter.…”
Section: Discussionsupporting
confidence: 66%
“…In the context of this discussion we should also mention that similar anomalous accelerations are also found in several spacecraft flybys of the Earth [3]. In this case, they are only a 1.5 % of those found in the case of the Juno's flybys of Jupiter.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies also reported slightly larger values of about 4cm/yr (Stephenson, 1981). It was proposed that these astrophysical anomalies may have some cosmological origin or may call upon new physical driving mechanisms not taken into account by traditional Newtonian physics and General Relativity (Acedo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we expect that β(D = R) 1 were R is the radius of the central body (the Earth in the case of the flybys) because during a flyby the spacecraft comes very close to the surface of the planet. In other numerical and analytical studies on the flyby anomaly, it has been suggested that the interaction responsible for these anomalies should diminish exponentially with altitude over the surface of the Earth [44]. A fact that is supported by a statistical analysis by Jouannic et al [45] which showed that the largest values for the flyby anomaly are largely correlated with the time the spacecraft stays below an altitude of 2000 km.…”
Section: The Anomalous Increase Of the Orbital Eccentricitymentioning
confidence: 85%
“…where D is the distance from the central or source body to the orbiting planet, satellite or spacecraft, and Λ is a characteristic length scale that depends of the physical parameters of the source. We can assume that Λ is proportional to the radius of the central body, Λ ∝ R. For the case of the Earth, and following previous work on the flyby anomaly [44,45] it seems that the characteristic length for this anomalous interaction is not much larger than the radius of the Earth. For example, if we take Λ Earth = 2.5R Earth we find from Eq.…”
Section: The Anomalous Increase Of the Orbital Eccentricitymentioning
confidence: 92%